IMPLEMENTASI KEBIJAKAN PENGAWASAN PINDAH LOKASI PENIMBUNAN MENGGUNAKAN ELECTRONIC SEAL(E-SEAL) PADA KANTOR BEA DAN CUKAI TANJUNG PRIOK - Yoan Agung Wibawa; Winda Wulandari (Jurnal Ilmu Administrasi Publik, 2025)
This study assesses the supervision of Transfer Location Storage (PLP) at the Tanjung Priok Customs Office through the use of GPS-enabled Electronic Seals (e-Seals). Method , A descriptive-qualitative design was employed. Data were gathered via in-depth interviews, field observations, and document analysis, and interpreted using George C. Edward III’s four-factor implementation model (communication, resources, disposition, and bureaucratic structure). E-Seals enhance the speed, transparency, and traceability of container movements; however, effectiveness is constrained by intermittent GPS signal loss, limited active devices, and sub- optimal coordination among operational units and vendors. Strengthening real-time communication channels, ensuring adequate buffer-stock of devices coupled with continuous technical training, and standardising emergency procedures are essential to fully realise the benefits of e-Seals in PLP supervision and to support national logistics efficiency Keywords e-Seal; PLP; policy implementation; Customs; logistics supervision